Barriers to clinical nurse participation in the internet-based home visiting program: a qualitative study - Jiahao Yu; Jianyuan Huang; Chunlei Li; Yongmei Zhuang (BMC, 2023)
Abstract Background Home visits are an important part of home care. With increasing demand and the rapid development of information technology, an increasing number of regions are experimenting with the use of information technology in home visits, hoping to meet the needs of more patients through technological interventions. However, most of the current studies have focused on patient health improvement through home visits, neglecting to consider the actual experience of nurses as service providers in participating in Internet-based programs. Thus, the purpose of this research is to explore what is holding nurses back from participating after the Internet has been added to traditional home visiting programs. Methods This research was designed with an exploratory-descriptive qualitative analysis method. Semistructured interviews were used to collect information on barriers to nurses' participation in the Internet-based home visiting program. Participants included 16 clinical nurses working in various hospitals in Nanjing, China. The thematic analysis method was used to analyze the information. Results This research identified three themes and twelve subthemes that hinder clinical nurse engagement in the Internet-based home visiting program. The three themes included multiple barriers to individuals, different service modes, and emerging organizational problems. Conclusions As a new form of traditional home visiting program in information society, Internet-based home visiting has many shortcomings in the overall program design and service management specifications. For more patients living at home to receive quality care services, it is necessary to take more effective measures to encourage nurses' participation at three levels: nurse demand, service process, and organizational management.